(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Ira R. Agasieva, Gulnara B. Mamedova (Makhachkala, Dagestan Republic, Russian Federation) In the article the problem of quality of teaching and knowledge of the English language has been considered. The factors that influence the improvement of the quality of teaching and knowledge of the English language in a technical college, the use of various methods of enhancing the quality of teaching and knowledge of the English language has been analyzed. It has been distinguished the necessity of taking into account the factors such as emotional maturity of the student, the desire for success, student cognitive style, its consistency and independence. Key words: foreign language in a technical college, communicativeactivity approach, language competence, cultural studies competence, communicative competence, factors to improve the quality of foreign language teaching in technical colleges, development of all types of speech activity (reading, listening, speaking and writing) in unity and correlation.